Penelitian Energi di Indonesia ditinjau dari Perspektif Manajemen Risiko: Analisis Bibliometrik Berdasarkan Kata Kunci - Pranoto Effendi (Pusat Riset dan Inovasi Nasional, 2025)
Research into the energy sector from a risk management perspective is urgent, particularly in addressing the vulnerability of Indonesia's energy system to various risks. This research is expected to provide strategic solutions and policy recommendations to improve the resilience and reliability of the national energy sector. This article specifically aims to map research on risk management in the Indonesian energy sector through bibliometric analysis. A total of 34 selected articles that met the inclusion criteria were obtained through a systematic screening and search process in the Google Scholar Database. Overall, 84 keywords were used in the collection of articles, which were then further analyzed. Findings include, among others, the presence of many different individual researchers, indicating widespread interest but the lack of a stable research group. Second, temporally, an upward trend in the number of publications has been identified in recent years, indicating that this topic is increasingly relevant. In terms of publication type, articles are relatively evenly distributed across various journals, focusing on engineering, management, and policy. The results of the network mapping analysis using VOSviewer software based on keywords indicate that this research area remains very broad. These keywords are spread across 13 different thematic clusters, reflecting the many dimensions of risk management that remain to be explored. There is ample opportunity for researchers to conduct more in-depth exploration, and efforts are needed to determine a more precise and specific research focus to provide effective and applicable solutions to address the strategic challenges of Indonesia's energy sector resilience.